2007
DOI: 10.1590/s0004-282x2007000400025
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos clínicos e evolutivos da hidrocefalia na neurocisticercose

Abstract: RESUMO -Com o propósito de analisar os aspectos clínicos da hidrocefalia (HDC) na neurocisticercose (NCC), realizou-se o estudo retrospectivo de 47 prontuários de pacientes com HDC e NCC. Verificou-se que 70,2% eram homens, entre 21 e 50 anos. A hipertensão intracraniana (HIC) ocorreu em todos os pacientes, cefaléia (CEF) em 89,4%, meningoencefalite (ME) em 80,8% e distúrbios psíquicos (PSI) em 74,5%. A síndrome liquórica da NCC foi detectada em 65,9% pacientes. Além da HDC, as tomografias computadorizadas de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 22 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…In spite of that, the inflammation composed mainly by polymorphonuclear cells associated with edema, perivasculitis, and meningitis in BALB/c mice was significantly greater than what was observed in the C57BL/6 ones during the experimental period. Fragoso et al 9 , when inoculating BALB/c mice via intraperitoneal with T. crassiceps cysticerci, observed that they presented a greater parasitary burden than C57BL/6 mice and antigens from the parasite are enough to cause those reactions, even without the inflammatory reaction in the cavity [20][21][22] . The activation and proliferation of the microglia, which is named microgliosis, were discretely higher in C57BL/6 mice throughout the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of that, the inflammation composed mainly by polymorphonuclear cells associated with edema, perivasculitis, and meningitis in BALB/c mice was significantly greater than what was observed in the C57BL/6 ones during the experimental period. Fragoso et al 9 , when inoculating BALB/c mice via intraperitoneal with T. crassiceps cysticerci, observed that they presented a greater parasitary burden than C57BL/6 mice and antigens from the parasite are enough to cause those reactions, even without the inflammatory reaction in the cavity [20][21][22] . The activation and proliferation of the microglia, which is named microgliosis, were discretely higher in C57BL/6 mice throughout the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrocephalus is a major concern for patients with extraparenchymal neurocysticercosis, because ventricular-peritoneal shunts have been plagued with high rates of malfunction and risk of infection. The higher the number of surgical revisions needed, the higher the overall mortality [42, 43]. …”
Section: Discussionmentioning
confidence: 99%
“…The management of NCC-related hydrocephalus is also more challenging than that of hydrocephalus of other etiologies because of the higher rates of shunt malfunction, infection, and the need for reoperation. [8][9][10][11] Albendazole is a well-established drug for the treatment of neurocysticercosis. Although some controversy regarding the safety of albendazole in the treatment of extraparenchymal NCC has arisen in the last decades, albendazole remains the drug of choice even for giant extraparenchymal cysts with a mass effect.…”
Section: Introductionmentioning
confidence: 99%